Spain : Financial Sector Assessment Program; Technical Note; Supervision of Insurance; Alternative Models for an Independent Agency. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report is the summary of a technical note on Supervision of Insurance of Spain and Alternative Models for an Independent Agency. It reviews the organizational alternatives for insurance supervision and discusses the advantages and disadvantages of alternative institutional arrangements. It presents various alternatives for an independent insurance supervisory agency for Spain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Spain